2019
DOI: 10.1186/s12870-019-2116-0
|View full text |Cite
|
Sign up to set email alerts
|

Rice defense responses are induced upon leaf rolling by an insect herbivore

Abstract: BackgroundPlant defense against herbivores begins with perception. The earlier plant detects the harm, the greater plant will benefit in its arm race with the herbivore. Before feeding, the larvae of the rice pest Cnaphalocrocis medinalis, initially spin silk and fold up a leaf. Rice can detect and protect itself against C. medinalis feeding. However, whether rice could perceive C. medinalis leaf rolling behavior is currently unknown. Here, we evaluated the role of leaf rolling by C. medinalis and artificial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Previously, it has been demonstrated that application of methyl jasmonate (MeJA) and methyl salicylate (MeSA) as topical sprays onto rice plants significantly improve rice defense against C. medinalis [ 14 , 15 ]. Recently, it was found that rice leaf rolling by C. medinalis larvae, but not by artificial leaf rolling, attracts the parasitoid Itoplectis naranyae as an indirect defense [ 16 ]. It is well known that plant response to herbivore damage is a dynamic process and that this process is associated with large-scale change at the mRNA, protein, and metabolite levels [ 5 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been demonstrated that application of methyl jasmonate (MeJA) and methyl salicylate (MeSA) as topical sprays onto rice plants significantly improve rice defense against C. medinalis [ 14 , 15 ]. Recently, it was found that rice leaf rolling by C. medinalis larvae, but not by artificial leaf rolling, attracts the parasitoid Itoplectis naranyae as an indirect defense [ 16 ]. It is well known that plant response to herbivore damage is a dynamic process and that this process is associated with large-scale change at the mRNA, protein, and metabolite levels [ 5 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, JAs function as chemical triggers to induce the biosynthesis of various defensive chemicals and proteins to counter pathogens and herbivores. Plant pattern-recognition receptors (PRRs) perceive molecular patterns from pathogens and herbivores to recognize herbivore-associated molecular patterns (HAMPs), damage-associated molecular patterns (DAMPs), and microbe/pathogen-associated molecular patterns (MAMPs/PAMPs) and thereby initiate JA signaling-dependent resistance [29,30]. These plant elicitor molecules can be peptides such as systemin, extracellular ATP (eATP), sucrose, volicitin, fatty acid conjugates, caeliferins and others [31,32].…”
mentioning
confidence: 99%
“…However, we show that assessing the order of attack is necessary to best understand the complexity and mechanisms of plant-insect-pathogen interactions. Moreover, our study suggests complete pathways must be characterized as differences are evident even when a few transcripts and metabolites are analyzed., often measured with associated gene transcripts (Bedini, Mercy, Schneider, Franken, & Lucic-Mercy, 2018; Ángeles-López el al., 2016; Shi et al, 2019), may fail to capture mechanisms by which plants interact with multiple stressors. Our results demonstrate both the order of arrival, and the diversity of interactions, determine plant responses to stress through the combined action of defense gene activation, phytohormone accumulation, and modification of plant nutrients.…”
Section: Discussionmentioning
confidence: 99%